2014
DOI: 10.11607/ofph.963
|View full text |Cite
|
Sign up to set email alerts
|

Patient Education and Self-Care for the Management of Jaw Pain upon Awakening: A Randomized Controlled Clinical Trial Comparing the Effectiveness of Adding Pharmacologic Treatment with Cyclobenzaprine or Tizanidine

Abstract: The use of tizanidine or cyclobenzaprine in addition to self-care management and patient education was not more effective than placebo for the management of patients with myofascial jaw pain upon awakening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…Sixteen studies had high risk of bias (Figure ) and were excluded from analysis (Table ). The remaining 41 studies rated as medium or low risk of bias were included in the qualitative analysis for the individual groups: 15 studies on patients classified as TMD‐joint , nine on patients classified as TMD‐muscle and 17 on patients with BMS .…”
Section: Results Of the Systematic Review And Network Meta‐analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Sixteen studies had high risk of bias (Figure ) and were excluded from analysis (Table ). The remaining 41 studies rated as medium or low risk of bias were included in the qualitative analysis for the individual groups: 15 studies on patients classified as TMD‐joint , nine on patients classified as TMD‐muscle and 17 on patients with BMS .…”
Section: Results Of the Systematic Review And Network Meta‐analysismentioning
confidence: 99%
“…For the TMD‐muscle group, nine relevant studies were identified . One study had to be excluded from the NMA because only change in relation to placebo was reported, which did not allow inclusion in the network of evidence.…”
Section: Results Of the Systematic Review And Network Meta‐analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The group acknowledged that in one study SM with medication had a better short‐term outcome than SM alone for jaw muscle pain . This effect, may, however depend on the type of muscle pain , and medication's usage has the undesired potential for patients to believe that the medication, and not the SM, has reduced their pain.…”
Section: Resultsmentioning
confidence: 99%